ANALYSIS OF RETURN ON EQUITY, CURRENT RATIO AND DEBT TO EQUITY RATIO TO CHANGES IN PROFIT IN SHARIA ISSUERS JAKARTA ISLAMIC INDEX - Mukhlisul Muzahid; Aryati; Lukman (RADJA PUBLIKA, 2022)
This study aims to examine and analyze Return On Equity, Current Ratio and Debt to Equity Ratio which have a significant effect on changes in earnings. This study uses a quantitative descriptive approach, the data used is panel data, with panel data regression analysis method as a data processing tool. Total population of 45 companies, research samples using purposive sampling obtained as many as 18 samples. The data was first tested by classical assumptions, normality test, multicollinearity test and heteroscedasticity test, panel data regression test and hypothesis testing using simultaneous test and partial test with a significant value of 0.05. The results showed that simultaneously Return On Equity, Current Ratio and Debt to Equity Ratio have a significant effect on earnings changes. partially Return On Equity and Current Ratio have a positive and significant effect on earnings changes, while the Debt to Equity Ratio has no significant effect on earnings changes. The results of the Adjusted R Square test show that the variation in the dependent variable is changes in earnings which can be explained by Return On Equity, Current Ratio and Debt to Equity Ratio of 41% while the remaining 59% can be explained by other variables outside this study.